The future of the Peruvian population: problems and opportunities - Aramburú, Carlos E. (2015)
This paper presents the trends and characteristics of the Peruvian population up to 2050 based both on official statistics and author’s estimates. Issues discussed include growth, changes in vital rates, age structure, the demographic bonus, ageing, migration and distribution. Policy implications of these demographic trends are also discussed.